Interesterification of rapeseed oil with methyl acetate in the presence of potassium tert-butoxide solution in tetrahydrofuran. (October 2020) - Kampars, Valdis; Abelniece, Zane; Lazdovica, Kristine; Kampare, Ruta
Abstract: Production of biodiesel (FAME) via transesterification of triglycerides with methanol in the presence of basic catalysts has largely increased over time despite the low value of the by-product glycerol. Interesterification of the same feedstock with methyl acetate allows to obtain biofuel with higher yield, as the by-product of this reaction, i.e. triacetin, can be included into the fuel composition. Investigation of interesterification with methyl acetate to oil molar ratio 18 at 55 °C during 1 h in presence of potassium tert -butoxide solution in tetrahydrofuran shows that after catalyst to oil molar ratio 0.1 slow increase of FAME and a decrease of triacertin content occur. Variation of catalyst to oil molar ratio does not allow to lower the content of intermediates below 19 wt%. An increase of methyl acetate to oil molar ratio from 18 to 65 reduces the mass fraction of intermediates to 9.5% and FAME to triacetin mass ratio to 5.2. The fuel characteristics of obtained products are close to or comply with the requirements of LVS EN 14214, excluding the requirements for FAME and intermediate content and density. The optimal region of methyl acetate to oil molar ratio as the reasonable compromise between the yield of the target products and removable excess of reactant could be from 24 to 40. Graphical abstract: Conversion of glycerol via interesterification of triglycerides. Image 1 Highlights: An optimal region of methyl acetate to oil molar ratio is between 24 and 40. Catalyst destroys triacetin and forms glycerol derivatives with hydroxyl groups. Full conversion of oil yields fuel that comply with main requirements for biodiesel.